Diseño y validación de un cuestionario de frecuencia de consumo de alimentos con azúcar para adultos en Quito, Ecuador - Manzano Alajo, Margareth Indira (2018)
The evaluation of dietary intake in individuals is essential to understand the association of dietary patterns with certain chronic noncommunicable diseases. There are several methods that allow us to know this information, one of the most used methods are the food frequency questionnaire, being it is a simple and low cost method. However, one of its disadvantages is the need to be validated before its application. It is for this reason that the objective of this study was to design and validate a food frequency questionnaire with sugars for adults in Quito, Ecuador. A questionnaire was designed with 74 food items with serving sizes and 9 frequency response options, which was applied to 25 healthy adults of both sexes aged between 19 and 60 years whose average age was 26 more less 8 years. The questionnaire was applied twice in a month to establish reproducibility. At the same time, the 24-hour reminder was applied to determine its validity. The correlation coefficients for estimating reproducibility range between 0.92 and 0.79 for total sugars and added sugars respectively. For validity, the correlation coefficients between the questionnaire and the 24-hour reminder for total sugars was 0.58 and for added sugars it was 0.63. In conclusion, the food frequency questionnaire with sugars was appropriate for the target population, since it was easy to understand and apply and allowed to evaluate the consumption of sugar since it showed considerable positive validity and average positive reproducibility.